ANALISIS KESEIMBANGAN ANTARA BIAYA AKIBAT RISIKO MEROKOK DAN PENDAPATAN CUKAI ROKOK UNTUK KESEJAHTERAAN MASYARAKAT - -, Hardiwinoto (VALUE ADDED | MAJALAH EKONOMI DAN BISNIS, 2008)
Objective this research is comparative between cigarettes risk cost with income from cigarettes cukai.The tools used are comparative analysis. There are two variables, that income cukai and cigarettes risk. There are three hypothetic that, first income cukai < than cigarettes risk cost, second income cukai = cigarettes risk cost, and third, income cukai > cigarettes risk cost.This research result two concludes that first, if only account formal income and cost data founded income cukai > cigarettes risk cost. Second, if is accounted uncontrolled cost founded income cukai > cigarettes risk cost.